Answer:
4 days is the correct answer
Step-by-step explanation:
9514 1404 393
Explanation:
We can start with the relations ...
![\displaystyle\left(x+\frac{1}{x}\right)^3=\left(x^3+\frac{1}{x^3}\right)+3\left(x+\frac{1}{x}\right)\\\\\left(x+\frac{1}{x}\right)^5=\left(x^5+\frac{1}{x^5}\right)+5\left(x^3+\frac{1}{x^3}\right)+10\left(x+\frac{1}{x}\right)\\\\\textsf{From these, we can derive ...}\\\\x^5+\frac{1}{x^5}=\left(x+\frac{1}{x}\right)^5-5\left(\left(x+\frac{1}{x}\right)^3-3\left(x+\frac{1}{x}\right)\right)-10\left(x+\frac{1}{x}\right)](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cleft%28x%2B%5Cfrac%7B1%7D%7Bx%7D%5Cright%29%5E3%3D%5Cleft%28x%5E3%2B%5Cfrac%7B1%7D%7Bx%5E3%7D%5Cright%29%2B3%5Cleft%28x%2B%5Cfrac%7B1%7D%7Bx%7D%5Cright%29%5C%5C%5C%5C%5Cleft%28x%2B%5Cfrac%7B1%7D%7Bx%7D%5Cright%29%5E5%3D%5Cleft%28x%5E5%2B%5Cfrac%7B1%7D%7Bx%5E5%7D%5Cright%29%2B5%5Cleft%28x%5E3%2B%5Cfrac%7B1%7D%7Bx%5E3%7D%5Cright%29%2B10%5Cleft%28x%2B%5Cfrac%7B1%7D%7Bx%7D%5Cright%29%5C%5C%5C%5C%5Ctextsf%7BFrom%20these%2C%20we%20can%20derive%20...%7D%5C%5C%5C%5Cx%5E5%2B%5Cfrac%7B1%7D%7Bx%5E5%7D%3D%5Cleft%28x%2B%5Cfrac%7B1%7D%7Bx%7D%5Cright%29%5E5-5%5Cleft%28%5Cleft%28x%2B%5Cfrac%7B1%7D%7Bx%7D%5Cright%29%5E3-3%5Cleft%28x%2B%5Cfrac%7B1%7D%7Bx%7D%5Cright%29%5Cright%29-10%5Cleft%28x%2B%5Cfrac%7B1%7D%7Bx%7D%5Cright%29)
![\displaystyle x^5+\frac{1}{x^5}=\left(x+\frac{1}{x}\right)^5-5\left(x+\frac{1}{x}\right)^3+5\left(x+\frac{1}{x}\right)\right)\\\\x^5+\frac{1}{x^5}=3^5 -5(3^3)+5(3)\\\\=((3^2-5)3^2+5)\cdot3=(4\cdot9+5)\cdot3=(41)(3)\\\\=\boxed{123}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%5E5%2B%5Cfrac%7B1%7D%7Bx%5E5%7D%3D%5Cleft%28x%2B%5Cfrac%7B1%7D%7Bx%7D%5Cright%29%5E5-5%5Cleft%28x%2B%5Cfrac%7B1%7D%7Bx%7D%5Cright%29%5E3%2B5%5Cleft%28x%2B%5Cfrac%7B1%7D%7Bx%7D%5Cright%29%5Cright%29%5C%5C%5C%5Cx%5E5%2B%5Cfrac%7B1%7D%7Bx%5E5%7D%3D3%5E5%20-5%283%5E3%29%2B5%283%29%5C%5C%5C%5C%3D%28%283%5E2-5%293%5E2%2B5%29%5Ccdot3%3D%284%5Ccdot9%2B5%29%5Ccdot3%3D%2841%29%283%29%5C%5C%5C%5C%3D%5Cboxed%7B123%7D)
Answer: x=2
3x−9x+7−3=−8
Step 1: Simplify both sides of the equation.
3x−9x+7−3=−8
3x+−9x+7+−3=−8
(3x+−9x)+(7+−3)=−8
−6x+4=−8
−6x+4=−8
−6x+4−4=−8−4
−6x=−12
−6x
−6
=
−12
−6
x=2
Answer:
X=73/7
Step-by-step explanation:
X + (x + 1) + (x + 2) = 126
3x = 123
x = 41
So the sides are 41, 42 and 43